(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This research paper presents a comprehensive examination of the methodological and pedagogical foundations for creating educational tasks through the use of quest technology. It investigates the theoretical background of quest-based learning, highlighting its psychological, didactic, and methodological dimensions that ensure effective application in the learning process. The study underscores the significance of quest technology in enhancing students’ motivation, stimulating creativity, and cultivating independent as well as critical thinking skills. As a contemporary learner-oriented method, quest technology combines the advantages of game-based and problem-based learning, contributing to innovation and interactivity in modern education.